(untitled) (Research, Society and Development, 2021)
The work consists of knowing the aspects of the natural diet of Trichiurus lepturus since it has great commercial value for the state of Maranhão. The species analyzed came from commercial fishing, which was captured in the municipality of Raposa - MA, between January and December 2019. A total of 144 organisms were studied. The frequencies of numerical and biomass occurrence and Relative Importance Index (RII) in the diet were calculated for each prey species. As for the food items present in the species’ diet, a diet was observed based on fish, unidentified items, sardines (Sardinella brasiliensis), and penaeid shrimp. The region under study can be characterized as a feeding place for the species. It has a diet composed of neritic organisms with pelagic habits associated with coastal and estuarine areas, fish item being the most specific items in the diet. It was observed that during the dry season (July to December), when biological productivity is low, feeding activity increases. The male’s diet is based on fish rest, while the female’s unidentified items is dominant. All immature males had their stomachs filled, and females had many unidentified items.